Analisis Faktor yang Mempengaruhi Kepuasan Wisatawan pada Ekowisata Hutan Mangrove di Desa Gosong Telaga Selatan Kecamatan Singkil Utara Kabupaten Aceh Singkil Tahun 2023 - Rusti Kurnia Mora Sinamo; Rusmauli Simbolon; Elvri Teresia Simbolon; Tio R. J Nadeak; Maringan Sinambela (Nawasena: Jurnal Ilmiah Pariwisata, 2024)
This research aims to analyze tourist satisfaction in Ekowisata Hutan Mangrove in Gosong Telaga Selatan village, North Singkil District, Aceh Singkil Regency in 2023. This research uses a descriptive quantitative approach by distributing questionnaires to 60 respondents using purpose sampling whose validity and reliability have been tasted. The results of descriptive statistical analysis were an average of 3.34. The percentage of achievement of the analysis of factors that influence tourist satisfaction in Ekowisata Hutan Mangrove in Gosong Telaga Selatan Village, North Singkil District, Aceh Singkil Regency in 2023 is 83.52% consulted with the interpretation criteria of a very satisfied score. The results of hypothesis testing t_count > t_tabel (8.71 > 0.2542) show that tourist satisfaction with Ekowisata Hutan Mangrove in Gosong Telaga Selatan Village, North Singkil District, Aceh Singkil Regency in 2023 is ≥ 75% of what was expected. The results of the research explain that tourist satisfaction with Ekowisata Hutan Mangrove in Gosong Telaga Selatan Village, North Singkil District, Aceh Singkil Regency in 2023 is ≥ 75% of what was expected.